Autoimmune myopathies: diagnosis and management review - Bertorini, Tulio (2019)
Idiopathic inflammatory myopathies (MII) are a group of autoimmune diseases that mainly affect the proximal muscles. The most common types are Dermatomyositis (DM), Polymyositis (PM), Necrotizing autoimmune myopathy and Inclusion body myositis. Unique forms are identified in their clinical presentation consisting of muscular and extramuscular manifestations, their myopathic alterations in the electromyogram and the elevation of muscle enzymes. However, muscle biopsy remains the gold standard for diagnosis. These disorders are tratable with a proper. The goals of treatment are to eliminate inflammation, restore muscle performance, reduce morbidity and improve quality of life.This review aims at a basic diagnostic approach in patients with suspicion of MMI through its main clinical, laboratory and histopathological findings.